1997
DOI: 10.1094/phyto.1997.87.7.693
|View full text |Cite
|
Sign up to set email alerts
|

Populations of Nonpathogenic Fusarium oxysporum Associated with Roots of Four Plant Species Compared to Soilborne Populations

Abstract: The effect of the plant on the diversity of soilborne populations of Fusarium oxysporum was assessed after successive cultures of flax, melon, tomato, and wheat in separate samples of the same soil. Forty soil-borne isolates of F. oxysporum and forty root-colonizing isolates of each plant species were sampled during the first (T0) and fourth (T1) cultures. The population structures were assessed by a genotypic method based on restriction fragment analysis of polymerase chain reaction-amplified ri-bosomal inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 18 publications
2
55
0
4
Order By: Relevance
“…In the first place, the great differences observed between the root fungal colonizers and those dwelling few centimeters apart in the rhizospheric soil would indicate specific adaptations either by certain fungi to enter and extend within plant tissues or by the host plant to trim among the soilborne-to-endophyte candidates. The latter capacity has been already observed in some plant species [32], and roots of Inula species (including the ones studied here) are known to produce antimicrobial metabolites that may affect their colonization by fungal endophytes (e.g., [33,34]). Fungi also differ broadly in their ability to invade plant tissues, and probably, the final selection of root colonizers is the result of both plant barriers and fungal capabilities.…”
Section: Discussionsupporting
confidence: 64%
“…In the first place, the great differences observed between the root fungal colonizers and those dwelling few centimeters apart in the rhizospheric soil would indicate specific adaptations either by certain fungi to enter and extend within plant tissues or by the host plant to trim among the soilborne-to-endophyte candidates. The latter capacity has been already observed in some plant species [32], and roots of Inula species (including the ones studied here) are known to produce antimicrobial metabolites that may affect their colonization by fungal endophytes (e.g., [33,34]). Fungi also differ broadly in their ability to invade plant tissues, and probably, the final selection of root colonizers is the result of both plant barriers and fungal capabilities.…”
Section: Discussionsupporting
confidence: 64%
“…The latter can colonize the cortex of plant roots without causing disease symptoms (Appel and Gordon, 1994), surviving in live tissues. They may also cause antagonism between pathogenic forms in the soil (Edel et al, 1997). Fusarium species are common pathogens of wheat and barley, causing various diseases: foot and root rot, crown rot, and Fusarium head blight (FHB).…”
Section: Introductionmentioning
confidence: 99%
“…These novel sequence types suggest that focusing only on plant-pathogenic F. oxysporum may underestimate the total species diversity. Other studies indicate that F. oxysporum populations from soil are geographically heterogeneous and greatly influenced by resident plant populations (19,20,21), suggesting that some plants may exert a selective effect on soil populations of F. oxysporum (22). Studies comparing pathogenic and nonpathogenic F. oxysporum populations associated with the same host have found much higher levels of diversity in the nonpathogenic populations than in the pathogens (11,14,23,24).…”
mentioning
confidence: 99%
“…Also, different genotypes may interact with their host plants in different ways; for example, studies focusing on developing nonpathogenic F. oxysporum fungi as biocontrol agents have found particular isolates to be better biocontrol agents than others (26,27,28). A few studies have reported overrepresentation of a few genotypes within endophytic populations (12,22), suggesting a possible selective effect by the host on soil populations.…”
mentioning
confidence: 99%